Are Islamic Gold-Backed Cryptocurrencies Bridging Digital and Traditional assets in OIC Emerging Markets? - Rahardjo, Joana Vevila; Anddromeda, Fanessa; Kurniawati, Graciella Jeanne Aretha; Havidz, Shinta Amalina Hazrati (Organizations and Markets in Emerging Economies, 2025)
This research explores the financial role of Hello Gold (HGT) and X8X Token (X8X) as Islamic gold-backed cryptocurrencies to bridge digital (Bitcoin, Ethereum, UCRY Price, UCRY Policy, and ICEA) and traditional (conventional stock indexes, government bonds, foreign exchange, and Islamic stock indexes) assets. Quantile via moment by Machado and Santos Silva (2019) was utilized as the main methodology, followed by a feasible generalized least square (FGLS) and a difference generalized method of moment (Diff-GMM) as robustness testing. The research term spanned from August 6, 2018 until June 30, 2023 within five emerging countries in the Organization of Islamic Cooperation (OIC) including Nigeria, Turkey, Indonesia, Malaysia, and Pakistan. It was found that Hello Gold and X8X Token primarily bridge the function as strong diversifiers, particularly for Bitcoin and Ethereum. However, Hello Gold performs strongly as a safe haven for Islamic stock indexes in bearish conditions and as a strong diversifier during high cryptocurrency price uncertainty.